Sandhi externe en macédonien et en roumain. Les assimilations de sonorité - Cychnerska, Anna (Studia Romanica Posnaniensia, 2020)
The paper presents a comparative analysis of the assimilation in terms of voicing on the border between words in Macedonian and in Romanian. Although the compared languages belong to different language families, the pronunciation of the obstruental segments in this position is similar. In both Romanian and Macedonian, a regular regressive assimilation is observed on the border between two words. In Macedonian, the voiced obstruent at the end of a word can be pronounced as a voiced or a voiceless before a resonant at the beginning of the next word. It is important that more often the voiced obstruent at the end of the word loses voicing before a vowel in the initial position than before a sonant. In Romanian, before a resonant in the initial position, the voiced obstruent in the final position of the word in front of it is pronounced voiced. The voiceless obstruent on the border between words can be pronounced as a voiced if it occurs before a sonant in the initial position of the next word. This is an optional phenomenon like the voiceless pronunciation of the voiced obstruent before a resonant on the border of two words in Macedonian. As one can see, in both languages, obstruents at the end of a word behave differently before initial vowels and sonants on the inter-word border.